Mastering Entity Framework Core 2.0 : Dive into entities, relationships, querying, performance optimization, and more, to learn efficient data-driven development. - Anbazhagan, Prabhakaran (Packt Publishing, 2017)
Being able to create and maintain data-oriented applications has become crucial in modern programming. This is why Microsoft came up with Entity Framework so architects can optimize storage requirements while also writing efficient and maintainable application code. This book is a comprehensive guide that will show how to utilize the power of ...